Population abundance and growth rate of western gray whales Eschrichtius robustus - Bradford, Amanda L.; Weller, David W.; R. Wade, Paul; Burdin, Alexander M.; Brownell, Robert L., Jr. (DigitalCommons@University of Nebraska - Lincoln, 2008)
The western population of gray whales Eschrichtius robustus is one of the most endangered whale populations in the world. Recent studies of this population off the northeastern coast of Sakhalin Island, Russia, have produced a photographic dataset that was utilized for the first mark-recapture assessment of western gray whale abundance. Given encounter histories of 129 individually identified whales spanning 25 monthly capture occasions from 1997 to 2003, a closed capture estimator was employed to estimate the number of individuals using the study area in each year. Temporary emigration probabilities were then applied to the closed capture estimates to enumerate the total population size of whales off northeastern Sakhalin Island. Total abundances from 1997 to 2003 were estimated as 64 ± 5.1 (SE), 55 to 75 (95% CI); 75 ± 4.9,66 to 85; 86 ± 3.1, 80 to 93; 77 ± 4.7, 68 to 87; 91 ± 3.4, 84 to 98; 98 ± 4.1, 90 to 106; and 99 ± 4.9, 90 to 109, respectively. These abundance estimates, particularly the last values in the series, most likely approximate the size of the entire western gray whale population. For comparison to the trend in the abundance estimates, life history data were used to estimate the growth rate of the population. Depending on the range of potential fecundity values incorporated, the resulting growth rate estimates indicate an annual population increase that is between 2.5 and 3.2 %. The extremely small population size and slow rate of increase documented here further highlight concern about the viability of this critically endangered population.